Mutation analysis of cell-free DNA and single circulating tumor cells in metastatic breast cancer patients with high CTC counts - Shaw,JA; Guttery,DS; Hills,A; Fernandez-Garcia,D; Page,K; Rosales,BM; Goddard,KS; Hastings,RK; Luo,J; Ogle,O; Woodley,L; Ali,S; et al. (Clinical Cancer Research, 2017)
Purpose: The purpose of this study was to directly compare mutation profiles in multiple single CTCs and cfDNA isolated from the same blood samples taken from patients with metastaic breast cancer (MBC). We aimed to determine whether cell-free DNA would reflect the heterogeneity observed in 40 single CTCs. Experimental design: CTCs were enumerated by Cellsearch. CTC count was compared with the quantity of matched cfDNA and serum CA15-3 and alkaline phosphatase (ALP) in 112 patients with metastatic breast cancer. In 5 patients with {greater than or equal to}100 CTCs, multiple individual EpCAM-positive CTCs were isolated by DEPArray and compared with matched cfDNA and primary tumour tissue by targeted next generation sequencing (NGS) of ~2200 mutations in 50 cancer genes. Results: In the whole cohort, total cfDNA levels and cell counts ({greater than or equal to}5 CTCs) were both significantly associated with overall survival, unlike CA15-3 and ALP. NGS analysis of 40 individual EpCAM-positive CTCs from 5 patients with MBC revealed mutational heterogeneity in PIK3CA, TP53, ESR1 and KRAS genes between individual CTCs. In all 5 patients cfDNA profiles provided an accurate reflection of mutations seen in individual CTCs. ESR1 and KRAS gene mutations were absent from primary tumour tissue and therefore likely reflect either a minor sub-clonal mutation or were acquired with disease progression. Conclusion: Our results demonstrate that cfDNA reflects persisting EpCAM-positive CTCs in patients with high CTC counts and therefore may enable monitoring of the metastatic burden for clinical decision-making.Experimental Design: DNA methylation was investigated in independent tumor cohorts using Illumina HumanMethylation arrays and gene expression by Affymetrix arrays and qRT-PCR. The role of Msh homeobox 1 (MSX1) in drug sensitivity was investigated by gene reintroduction and siRNA knockdown of ovarian cancer cell lines.Results: CpG sites at contiguous genomic locations within th